Effect of Mucuna pruriens on brain NMDA receptor and tau protein gene expression in cerebral ischemic rats - Parvatikar, Prachi P.; Patil, S. M.; Patil, Bheemshetty S.; Reddy, R. Chandramouli; Bagoji, Ishwar; Kotennavar, Manjunath S.; Patil, Sumangala; Patil, Aravind V.; Das, Kusal K.; Das, Swastika N.; Bagali, Shrilaxmi (Frontiers in Physiology, 2023)
Present study aimed to assess effect of pre-treatment with Mucuna pruriens seed extract and its bioactive molecule(s) on NMDAR and Tau protein gene expression in cerebral ischemic rodent model. Methanol extract of M. pruriens seeds was characterized by HPLC, and β-sitosterol was isolated by flash chromatography. In vivo studies to observe the effect of pre-treatment (28 days) with methanol extract of M. pruriens seed and β-sitosterol on the unilateral cerebral ischemic rat model. Cerebral ischemia induced by left common carotid artery occlusion (LCCAO) for 75 min (on day 29) followed by reperfusion for 12 h. Rats (n = 48) divided into four groups. GroupI (control,Untreated + LCCAO)-No pre-treatment + cerebral ischemia; GroupII(β-sitosterol + Sham)-pre-treatment with β-sitosterol, 10 mg/kg/day + sham-operated; GroupIII(β-sitosterol + LCCAO)-pre-treatment with β-sitosterol, 10 mg/kg/day + cerebral ischemia; GroupIV(methanol extract + LCCAO)-pre-treatment with methanol extract of M. pruriens seeds, 50 mg/kg/day + cerebral ischemia. Neurological deficit score was assessed just before sacrifice. Experimental animals were sacrificed after 12 h reperfusion. Brain histopathology was performed. Gene expression of NMDAR and Tau protein of left cerebral hemisphere (occluded side) was performed by RT-PCR. Results revealed that the neurological deficit score was lower in groups III and IV compared to group I. NMDAR and tau protein mRNA expression in left cerebral hemisphere were upregulated in Group I, downregulated in groups III and IV. Histopathology of left cerebral hemisphere (occluded side) in Group I showed features of ischemic brain damage. Groups III and IV, left cerebral hemisphere showed less ischemic damage compared GroupI. Right cerebral hemisphere showed no areas of ischemia-induced brain changes. Pre-treatment with β-sitosterol and methanol extract of M. pruriens seeds may reduce ischemic brain injury following unilateral common carotid artery occlusion in rats.